Flowers of the Forest Plants and People in the New Forest National Park. - Chatters, Clive (WILDGuides Ser., 2009)
This book explores the botanical richness and cultural heritage of the New Forest National Park in Hampshire, England. The New Forest has become an exceptional area for wildflowers, many of which were once common throughout the lowlands of Britain. The Forest enjoys strong populations of many special wildflowers because it retains a living tradition of free-ranging domestic animals grazing its coastland, extensive commons, and village greens. This book is an exploration of how the wildlife of the Forest is the natural expression of the lives and economy of the people of the Forest. An introduction to the New Forest and how its commoning economy works A description of the principal habitats of the Forest and how they relate to one another Accounts of the people who have explored the Forest for wildflowers from the early 17th century to the present Descriptions of more than 100 species of the rarer flowering plants and ferns currently known from the National Park, many of which are nationally or internationally rare, scarce, or threatened An account of Forest conservation issues by someone who has participated in the life of the Forest for more than 20 years.